Simulation safety management of IBS construction - Bashir, Abdullahi Abdullatif (2008)
Construction is one of the most hazardous industries due to its unique nature. Measured by international standards, construction site safety records in construction are poor. Many construction companies around the world are implementing safety, health, and environmental management systems to reduce injuries, eliminate illness, and to provide a safe work environment in their construction sites. The increase in both insurance costs and workers‘ compensation makes it necessary to reduce eliminate worksite accidents. The Occupational Safety and Health Act of 1970 were established to provide guidelines for safe worksite practices and to ensure the safety of the workers. One of the best ways to avoid injuries and minimize costs is through good planning and co-ordination – both before and on the job. On-site working conditions, lack of proper training, and improper use of safety equipment often lead to serious injury and even death. The involvement of scaffolds, ladders, heavy equipment and in some cases dangerous chemicals, greatly increase the risk of construction accidents.